2017
DOI: 10.1515/med-2017-0065
|View full text |Cite
|
Sign up to set email alerts
|

Aortic aneurysm as a complication of myeloperoxidase-antineutrophil cytoplasmic antibody-associated vasculitis

Abstract: AbstractMyeloperoxidase-antineutrophil cytoplasmic antibody-associated vasculitis (MPO-AAV) does not usually involve large vessels, such as the aorta. However, we experienced three cases having an aortic aneurysm as a complication of MPO-AAV with renal insufficiency. In one patient it involved the onset of descending aortic dissection during treatment for MPO-AAV; another two patients had an abdominal aortic aneurysm at the time of our diagnosis of MPO-AAV. Although we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“… 12 13 Although large vessel vasculitis is likely to be a consequence of BD involvement, AAV can also provoke large vessel vasculitis: so far, several case series have reported that large vessel vasculitis might be associated with AAV and have indicated that large vessel vasculitis can occur in a spectrum of various clinical features. 14 15 16 Thus, vascular manifestations that characterize large vessel vasculitis in ANCA-positive BD patients are likely to contributable to both BD and AAV. In our study, we did not notice any ANCA-positive BD patients who exhibited vena cava thrombosis or aorta involvement.…”
Section: Discussionmentioning
confidence: 99%
“… 12 13 Although large vessel vasculitis is likely to be a consequence of BD involvement, AAV can also provoke large vessel vasculitis: so far, several case series have reported that large vessel vasculitis might be associated with AAV and have indicated that large vessel vasculitis can occur in a spectrum of various clinical features. 14 15 16 Thus, vascular manifestations that characterize large vessel vasculitis in ANCA-positive BD patients are likely to contributable to both BD and AAV. In our study, we did not notice any ANCA-positive BD patients who exhibited vena cava thrombosis or aorta involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Through a search of AAV-related aortic aneurysm cases in the Pubmed database, together with the case of MPO-AAV combined with AAA that we reported, we found a total of 11 articles reporting 14 cases of AAV combined with aortic aneurysm(Table 1). [3][4][5][6][7][8][9][10][11][12][13] This included seven patients diagnosed with GPA-AAVand two patients with MPA, while the remaining five patients had no pathological results. Among these 14 cases, nine were abdominal aortic aneurysms and five were thoracic aortic aneurysms.…”
Section: Discussionmentioning
confidence: 99%